Pengaruh Kepemilikan Institusional, Financial Distress, dan Intensitas Modal terhadap Konservatisme Akuntansi - Narti Mariati; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to analyze the effect of institusional ownership, financial distress, and capital intensity on accounting conservatism in manufacturing companies listed on the Indonesia Stock Exchange for period 2018-2022. The Study used purposive sampling method, with 295 samples and 5 observation periods.The results showed that financial distress has a positive and significant effect on accounting conservatism, while institutional ownership and capital intensity have no significant effect on accounting conservatism. This study contributes to add insight and knowledge in the field of accounting, about the factors that influence accounting conservatism in manufacturing companies.